β-estradiol Induces Mitochondrial Apoptosis in Cervical Cancer through the Suppression of AKT/NF-ΚB Signaling Pathway - Huang, Yuqing; Chen, Shouguo; Lei, Yuhe; Chung, Chiwing; Chan, Meiching; Chen, Lei; Zhong, Yinqin; Zhang, Enxin; Chen, Jiaxu; Deng, Lijuan (Recent Patents on Anti-Cancer Drug Discovery, 2022)
Background: Cervical cancer is the fourth most prevalent gynecological cancer worldwide, which threatens women's health and causes cancer-related mortality. In the search for effective anticervical cancer drugs, we discovered that β-estradiol (E2), a potent drug for estrogen deficiency syndrome treatment, displays the most potent cytotoxicity against HeLa cells. Objective: This study aims to evaluate the growth inhibitory effect of β-estradiol on HeLa cells and explore its underlying mechanisms. Methods: CCK-8 assay was used to evaluate the cytotoxicity of 6 compounds against HeLa cells. Flow cytometric analysis and Hoechst 33258 staining assay were performed to detect cell cycle arrest and apoptosis induction. The collapse of the mitochondrial potential was observed by the JC-1 staining assay. The expression levels of proteins were examined by western blotting. Results: β-Estradiol, at high concentration, displays potent cytotoxicity against HeLa cells with an IC50 value of 18.71 ± 1.57 μM for 72 h treatment. β-Estradiol induces G2/M cell cycle arrest through downregulating Cyclin B1 and p-CDK1. In addition, β-estradiol-induced apoptosis is accompanied by the loss of mitochondrial potential, activation of the Caspase family, and altered Bax/Bcl-2 ratio. β-Estradiol markedly decreased the expression level of p-AKT and p-NF-ΚB. Conclusion: This study demonstrated that β-estradiol induces mitochondrial apoptosis in cervical cancer through the suppression of AKT/NF-ΚB signaling pathway, indicating that β-estradiol may serve as a potential agent for cervical cancer treatment.
Keywords: Cell Cycle Arrest